PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU PADA SMK NEGERI 1 KEMANG DI BOGOR - Alfiyanto, Fiqhi; Sina, Ibnu (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of the work environment on teacher performance at SMK Negeri 1 Kemang, Bogor Regency, to determine the influence of work motivation on teacher performance at SMK Negeri 1 Kemang, Bogor Regency, to determine the influence of the work environment and work motivation simultaneously on teacher performance at SMK Negeri 1 Kemang, Bogor Regency. The method used is quantitative. The sampling technique used saturated sampling, namely 52 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that the work environment has a significant effect on teacher performance with a coefficient of determination value of 52.9% and the hypothesis test obtained t count > t table or (7.491 > 2.009). Work motivation has a significant effect on teacher performance with a coefficient of determination value of 43.9% and hypothesis testing obtained t count > t table or (6.259 > 2.009). The work environment and work motivation simultaneously have a significant effect on teacher performance with the regression equation Y = 8.347 + 0.432X1 + 0.365X2. The coefficient of determination value is 61.5% while the remaining 38.5% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (39.160 > 2.790).